Inhibition of Colon Cancer Recurrence via Exogenous TRAIL Delivery Using Gel-like Coacervate Microdroplets - Sungjun Kim; Yerim Jwa; Jiyeon Hong; Kyobum Kim (Gels, 2022)
Colon cancer (CC) belongs to the three major malignancies with a high recurrence rate. Therefore, a novel drug delivery system that can prevent CC recurrence while minimizing side effects is needed. Tumor-necrosis-factor-related apoptosis-inducing ligand (TRAIL) has recently been spotlighted as a protein drug that can induce apoptosis of cancer cells specifically. However, its short in vivo half-life is still a challenge to overcome. Hence, in this study, a gel-like mPEGylated coacervate (mPEG-Coa) delivery platform was developed through electrostatic interaction of mPEG-poly(ethylene arginylaspartate diglyceride) (mPEG-PEAD) and heparin for effective protection of cargo TRAIL, subsequently preserving its bioactivity. mPEG-Coa could protect cargo TRAIL against protease. Sustained release was observed for a long-term (14 days). In addition, recurrence of HCT-116 cells was suppressed when cells were treated with TRAIL-loaded mPEG-Coa for 7 days through long-term continuous supply of active TRAIL, whereas re-proliferation occurred in the bolus TRAIL-treated group. Taken together, these results suggest that our gel-like mPEG-Coa could be utilized as a functional delivery platform to suppress CC recurrence by exogenously supplying TRAIL for a long time with a single administration.